A study of immunization status of children in the age group 2-5 years - Kurane, Anil B.; Swathi, Dokku (International Journal of Contemporary Pediatrics, 2018)
Background: An evaluation by UNICEF India coverage survey (2009) showed that in India, 61% of children are fully immunized which is significantly low. Objectives of this study were to determine Immunization status of children in the age group of 2 to 5 years and study the social factors influencing immunization status of a child. To know the reasons for partial and non-immunization and study relation of socio-economic status with immunization status. Methods: A total 2000 children aged 2-5 years who are attending Pediatric OPD, Immunization clinics and admitted in Pediatric ward between May 2015 to May 2017 are enrolled in the present study. Subjects were selected by Simple random sampling method. Immunization status of these children was analyzed and the cause for partial and un-immunization were studied. Results: Of 2000 children studied, 1303 (65.2%) were fully immunized,681 were partially immunized (34%) i.e the child had received at least one of the immunization mentioned in NIP and 16 of them were un-immunized (0.8%) i.e they had not received even a single vaccine. Conclusions: The present study of immunization coverage of 65.2% among children attending pediatric hospital is far from satisfactory. The goal of achieving even 85% coverage seems to be an uphill task. Adverse effects following immunization, busy parents, lack of knowledge seems to be a major contributing factor for the non-success of this national programme. Age, birth order, parent’s occupation. parent’s education, mother’s age are statistically significant contributing factors for the poor immunization coverage among these children.